Ultrasound for the generalist : a guide to point of care imaging - 4 0 16; Dr., Clare, Sarb,;Duncan, Chris; 5 (Cambridge, United Kingdom :;New York, NY : Cambridge University Press, 2022)
Point of care ultrasound (POCUS) has become an essential tool within acute specialties to enhance bedside diagnostics, facilitate safe interventional procedures and guide referral to specialist services. It is vital for this tool to be expanded to community and prehospital settings where access to definitive investigations is limited. With the evolution of technology, ultrasound is becoming increasingly available due to reducing costs, machine size and remote image review for quality assurance purposes. This skill is invaluable for clinicians at all levels of training from medical school through to consultancy and allied healthcare professionals in any discipline--
Physics, Knobology and Artefacts -- Echocardiography -- Thoracic Ultrasound -- Abdominal Ultrasound -- Vascular Ultrasound -- Soft Tissue and Musculoskeletal Ultrasound -- Ultrasound for Neurology -- Gynaecology and Early Pregnancy Ultrasound -- Hospital at Home -- Palliative Care -- Ultrasound in Prehospital, Remote and Austere Environments -- COVID-19 -A World Stage -- Governance and Quality Assurance -- Training and Accreditation.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; instrumentation;methods -- Ultrasonography;Ultrasonography;Point-of-Care Systems -- 20; 20; 2